Chloroquine and Hydroxychloroquine Myopathy: Clinical Spectrum and Treatment Outcomes - Naddaf, Elie; Paul, Pritikanta; AbouEzzeddine, Omar F. (Frontiers in Neurology, 2021)
Chloroquine (CQ) and hydroxychloroquine (HCQ) have been associated with muscle toxicity, mostly described as a proximal myopathy with evidence of lysosomal dysfunction on muscle biopsy. In this retrospective study, we aimed to define the clinical phenotype, laboratory features and treatment outcomes of CQ/HCQ-myopathy, as well as the safety profile of these drugs. We identified 13 patients seen between 2000 and 2019, with a median age at presentation of 66 years (range 53-89); 11were females. At onset of symptoms, patients were on CQ or HCQ for a minimum of 6 months and up to 21 years. Diagnosis was often delayed by a median of 6 months (range 3-48). At presentation, 13 patients reported limb weakness with 5 requiring assistance walking. Ten reported dysphagia, often severe, resulting in marked weight loss or aspiration pneumonia. Nine reported respiratory symptoms, which were multifactorial in four, and four reported severe neck weakness. Myopathy clinical phenotype showed predominant involvement of one or more of the following: proximal limb muscle weakness (12 patients), dysphagia (9), axial weakness (4), and respiratory failure (5). Two patients had also probable CQ/HCQ length-dependent peripheral neuropathy, often mild and sensory predominant. 11 patients had a cardiac evaluation showing prolonged QT interval in 10, and CQ/HCQ CMP in four. Ten out of 12 patients markedly improved after discontinuing the medication, but most left with some residual weakness. 11 patients had a muscle biopsy showing a myopathy with rimmed vacuoles and marked acid phosphatase reactivity. 9 had elevated creatine kinase level up to 1199 U/L. 12 had an EMG which showed myopathic units with fibrillation potentials in 11, and myotonic discharges in 3. Higher cumulative dose and longer exposure duration were associated with more severe disability, and more common cardiac and swallow involvement, indicating a cumulative dose effect. Herein, we demonstrate that long term exposure to CQ and HCQ may result in a myopathy with a wide spectrum of clinical presentation and predilection to swallowing, respiratory and cardiac muscles, often with marked associated morbidity. Once accurately diagnosed and the drug is discontinued, patients usually improve but often fail to return to baseline.